Use of reality capture technologies in the US construction industry - Karbasiahvazi, Ali, author; Olbina, Svetlana, advisor; Elliott, Jonathan W., advisor; Malinin, Laura, committee member (Colorado State University. Libraries, 2021)
The construction industry has traditionally been slow to adopt new technologies. Reality capture technologies (RCT), including laser scanning and photogrammetry, have been around for many years; however, the benefits, obstacles, and application areas of these technologies in the construction industry have not been investigated nor quantified in detail. Clarifying the benefits and obstacles to implementing RCT by different construction project stakeholders could encourage decision-makers to invest in these technologies for their projects. This study aimed to explore the use of RCT within the commercial building sector of the US construction industry. A survey was used to investigate the extent of RCT use, including different commercial project types and throughout project lifecycles, and the benefits and obstacles of using RCT. The survey was distributed to owners/developers, designers, contractors, and construction managers/owner representatives across the US. Descriptive statistics indicated that most survey participants were familiar with RCT. Using ANOVA and t-tests, statistical comparisons revealed no significant differences by project stakeholders regarding the proposed benefits or obstacles of RCT use in commercial building projects. However, results showed a statistically significant difference for RCT benefits by project type, suggesting that participants perceived RCT use was more beneficial for additions, renovations, or maintenance projects than new construction projects. Additionally, statistical analysis revealed that participants perceived the use of RCT was less beneficial during the operation and maintenance (O&M) phase compared to other phases of project lifecycle. This research contributes to the body of knowledge by providing perspectives of US construction project stakeholders regarding RCT use. RCT providers and manufacturers can use the research findings to better fit their products to the needs of construction project stakeholders. The findings can also help AEC firms in the commercial building sector to implement RCT on their projects.
Keywords: construction industry; photogrammetry; reality capture; laser scanning; commercial buildings; project stakeholders